Unsteady MHD Free Convection and Mass Transfer Flow Through a Vertical Oscillatory Porous Plate in a Rotating Porous Medium with Hall, Ion-slip Currents and Heat Source (Dhaka University Journal of Science, 2016)
The analytical solution is made on the unsteady flow of an electrically conducting viscous incompressible fluid bounded by an infinite vertical porous plate. The plate executes harmonic oscillation at a frequency n in its own plane. The governing equations of the problem contain coupled partial differential equations. The dimensionless equations are solved analytically using perturbation technique. The effect of various parameters of the problem on the velocity, temperature and concentration field within the boundary layer are discussed and shown graphically.Dhaka Univ. J. Sci. 64(2): 91-98, 2016 (July)